2015
DOI: 10.1038/onc.2015.470
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressor NFκB2 p100 interacts with ERK2 and stabilizes PTEN mRNA via inhibition of miR-494

Abstract: Emerging evidence from The Cancer Genome Atlas (TCGA) has revealed that nfκb2 gene encoding p100 is genetically deleted or mutated in human cancers, implicating NFκB2 as a potential tumor suppressor. However, the molecular mechanism underlying the anti-tumorigenic action of p100 remains poorly understood. Here, we report that p100 inhibits cancer cell anchorage-independent growth, a hallmark of cellular malignancy, by stabilizing the tumor suppressor PTEN mRNA via a mechanism that is independent of p100’s inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 50 publications
(63 reference statements)
4
31
0
Order By: Relevance
“…PTEN is a well-characterized tumor suppressor that contributes to the inactivation of the Akt signaling pathway and suppression of cell survival, cell proliferation, and oncogenic cellular transformation. 29 The p38 MAPK signaling pathway has been demonstrated to play a vital role in a number of physiological or pathological conditions, including cancer development. 30,31 A previously conducted study has reported that p38 promotes tumorigenesis by mediating tumor cell invasion and metastasis, and another study has shown that the p38 pathway functions as a tumor suppressor by inhibiting cell proliferation in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a well-characterized tumor suppressor that contributes to the inactivation of the Akt signaling pathway and suppression of cell survival, cell proliferation, and oncogenic cellular transformation. 29 The p38 MAPK signaling pathway has been demonstrated to play a vital role in a number of physiological or pathological conditions, including cancer development. 30,31 A previously conducted study has reported that p38 promotes tumorigenesis by mediating tumor cell invasion and metastasis, and another study has shown that the p38 pathway functions as a tumor suppressor by inhibiting cell proliferation in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The shRNA constructs specifically targeting mouse and human p52, AUF1, USP8, and Sp1 were purchased from Open Biosystems (Thermo Fisher Scientific, Pittsburgh, PA). Plasmids pBabe‐puro p100 (1‐900)/p52 (1‐442) were generously provided by Dr Han‐Fei Ding (Cancer Center, Georgia Regents University, Augusta, GA) and have been used in our published studies . Mouse Sp1 3′‐UTR luciferase reporter and Sp1 3′‐UTR point mutation luciferase reporters (with miR‐145, miR‐29c, and miR‐125b binding sites mutated) were cloned into pMIR report luciferase vector.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids pBabe-puro p100 (1-900)/p52 (1-442) were generously provided by Dr Han-Fei Ding (Cancer Center, Georgia Regents University, Augusta, GA) 27 and have been used in our published studies. 28 Mouse Sp1 3′-UTR luciferase reporter and Sp1 3′-UTR point mutation luciferase reporters (with miR-145, miR-29c, and miR-125b binding sites mutated) were cloned into pMIR report luciferase vector. Constructs expressing pFRT/TO/HIS/FLAG/HA-AUF1 29 and FLAG/HA-USP8 30 were obtained from Addgene (Cambridge, MA).…”
Section: Primary P52+/+ and P52−/− Mouse Embryonic Fibroblasts (Mefs)mentioning
confidence: 99%
“…Plasmids pBabe-puro p100 (1-900)/p52 (1–442) were generously provided by Dr. Han-Fei Ding (Cancer Center, Georgia Regents University, Augusta, GA) [19] and has been used in our published studies [49]. Mouse cyclin d1 3′-UTR luciferase reporter and cyclin d1 3′-UTR point mutation luciferase reporter (miR-302d binding site was mutated) were cloned into the pMIR report luciferase vector.…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was determined using Nano Drop 2000 (Thermo Scientific, Holtsville, NY, USA). The cell extract (60–80 μg/sample) was subjected to Western Blotting with specific antibodies as described in our previous studies [49]. The densitometry analyses of the protein bands were performed using the ImageQuant 5.2 software (GE Healthcare, Pittsburgh, PA).…”
Section: Methodsmentioning
confidence: 99%